Tax incentives during the Covid-19 pandemic: An Islamic economics perspective - Triwibowo, Ananto; Sugeng, Anggoro; Baidhowi, Muhammad Mujib (Universitas Islam Indonesia, 2023)
IntroductionThe economic impact of Covid-19 virus is also felt by the state revenue sector due to tax incentives.ObjectivesThis study aims to analyze the tax incentive policies implemented by the government during the Covid-19 pandemic in terms of objectives, impacts, and the concept of convenience from an Islamic economics perspective. MethodThis study uses a normative-juridical approach by examining tax incentive policies in the context of Islamic economic theory from philosophical and juridical perspectives.ResultsFrom an Islamic economic perspective, the existence of tax incentives seen from the objective of the results and benefits is appropriate because it creates maslahah in the midst of an emergency or critical situation. In addition, the convenience provided by the government in tax incentives if seen from Islamic law is rukshah, or convenience and understanding for citizens due to certain conditions, namely the Covid-19 pandemic. ImplicationsThis study contributes to the development of theoretical research in the field of macroeconomic policy from an Islamic perspective. This study can also be used as a reference by the government to provide tax incentives in times of similar crises.Originality/NoveltyThis study is unique in that it examines the problem of tax incentives from an Islamic perspective. As a country with the world's largest Muslim population, this study will enrich Islamic macroeconomic studies for policymaking in Indonesia.